The Influence of Flexible Working Arrangement on Employee Performance with Work Life Balance as a Mediation - Harjanti, Dhyah; Harryman, Ellen; Noerchoidah; Rossitika, Amanda Rizky (Universitas Dinamika, 2025)
Flexible working arrangement (FWA) is increasingly being implemented to improve operational efficiency and employee welfare. Technological advances support the implementation of FWA, but challenges in human resource management remain. Work-life balance is a key factor that influences employee performance in a flexible work system. The study analyzed the relationship between flexible working arrangements, work-life balance, and employee performance to better understand the mechanisms underlying this relationship. This study used purposive sampling with 305 respondents. Data were gathered by means of Google Form and analyzed using the SEM-PLS method. Flexible work arrangements have a positive but insignificant direct impact on employee performance. However, FWA significantly has positive impact on work-life balance, which in turn improves employee performance and enacts as a mediator in the correlation. This study found that FWA improves employee performance through work-life balance as a mediator. The implications of the study encourage the effective implementation of FWA, with recommendations for further research on demographic factors and industry sectors.